(untitled) (Indian Journal of Public Health Research & Development, 2020)
People who have high emotional intelligence create understanding or know how to manage their own emotions and they know how to read emotions of others. Emotional intelligence was positively connected to physical, psychosomatic and mental health. The studies on the predictors of emotional intelligence, particularly in India are limited. For this purpose focus of the present study was to investigate the predicting effect of personality traits (neuroticism & extraversion) on emotional intelligence among the student of Raipur, India. A sample of the study comprised 300 P.G. students (male=50; female=50). Mangal Emotional Intelligence Inventory and Eysenck’s Maudsley Personality inventory (M. P. I.) were used to measuring emotional intelligence (EI) and personality traits. SPSS 16th version, structure equation model (SEM) with ADANCO, jamovi. (Version 1.0) were used for analysis. Measurement model was excellent fit in the samples [CFI = .968, TLI=0.904, SRMR=.033 and RMSEA = 0.11 (RMSEA 90% CI: Lower-0.0495, Upper-0.189)]. The findings revealed that personality traits, neuroticism emerged as significant predictors of emotional intelligent, intra personal awareness, inter personal awareness and inter personal management. Age emerged as significant predictors of emotional intelligent and its dimension. The findings also revealed that gender and extraversion have no impact on emotional intelligent and its dimension. A stable personality, age and their psychological wellbeing are important in enhancing the emotional intelligence of young students as there is a possibility in improving their emotional intelligence.